Pengembangan strategi bisnis Melalui BMC (Business Model Canvas) dan strategi pemasaran bagi UMKM Sari Delight Surabaya - Candraningrat Candraningrat; Dhika Yuan Yurisma; Siti Mujanah (TEKMULOGI: Jurnal Pengabdian Masyarakat, 2021)
The purpose of this activity is to assist SMEs Sari Delight Surabaya to solf the problems they face in running their business effectively and schive the target. Some of the problems faced include capitalization, decreased sales, distribution, decreased production, difficulty in raw materials, and difficulty in selling. So that in this activity it provides the right solution, namely by compiling a Business Model Canvas (BMC) to analyze each block on BMC so that we can find out the problems and shortcomings that must be met. Developing a marketing strategy is also done using social media as a medium of sales, such as Instagram, WhatsApp and Go-Food for promotions and sales medium, because it makes it easier for MSMEs to sell their product, besides that, we also design attractive packaging and make videos for product promotion. In addition, this activity also provides e-commerce training in order to optimize the marketing channel media, so that sales increase. The results of this study are that the use of social media makes it easier for companies to carry out their promotional activities.